Impact of aerial deposition from thermal power plant on growth and yield of rice (Oryza sativa) and wheat (Triticum aestivum) - CHAKRABARTI, B; SINGH, R; BHATIA, A; SINGH, S D; SINGH, B (The Indian Journal of Agricultural Sciences, 2014)
Thermal power plants (TPP) are a major source of air pollutants particularly suspended particulate matter (SPM) which either remains suspended in air or gets deposited onto soil surface and crop canopy in adjoining areas thereby affecting the growth and productivity of crops. Keeping this in view, a study was undertaken near Dadri TPP situated at NTPC Dadri, Uttar Pradesh, to assess the impact of aerial deposition on crops grown in adjoining areas. Eight different locations situated in different villages located at varying distance within 1-10 km radius were selected for study. Rice (Oryza sativa L.) and wheat (Triticum aestivum L.) fields were identified in the selected villages and their growth and yield parameters were recorded during the entire crop duration. Aerial deposition load on crop canopy was also quantified. Results showed that rice and wheat crops grown nearer to the TPP were most affected in terms of reduction in growth and yield as compared to fields located at far off distances. This was attributed to the deposition of SPM on rice and wheat leaves, which reduced photosynthesis rate leading to lower leaf area index, biological and grain yield of both the crops. In wheat crop, aerial deposition load on leaves was found to be more than rice at all stages. Reduction in grain yield in rice within10 km radius were 13.5% and 20.4%, while in wheat reduction were 21.9% and 19.1% in first and second year of study, respectively. The zone of 1 to 3 km radius from the TPP was found to be most vulnerable in terms of yield loss both in rice and wheat crops. In this zone some more resistant alternative crops can be grown which will help farmers to increase their productivity and income.